Class Management As A Determinative Factor Toward Learning Result (A Study to Economic Subject Student High and Low Group in Public Senior High Schools in Singkawang) - Junaidi H. Matsum (STKIP Singkawang, 2016)
A special objective research: 1. Class management of XI IPS1 high group students and low group students among all Public Senior High Schools in Singkawang. 2. Study results of economic subjects from students XI IPS1 with high and low group in Public Senior High Schools in Singkawang. 3. Class management is a determinative factor of students’ learning result of high and low group in Public Senior High Schools in Singkawang. Urgency of the research: Practically for students: 1. Class management as an effort to improve student motivation in the learning process of economic subjects study. 2 .Improving students’ study result in economic subject .For teachers: 1. This research can give significant contribution for economic teachers in order to manage the class better. 2. Improving the quality of teaching and learning. For school: 1. Give contributions in improving quality of teachers. 2. Improving the rank of school success. Theoritically: The result of this research is expected to be able to increase teachers’ knowledge in general that is related to the theories about class management and study result.